2004
DOI: 10.1002/jemt.20055
|View full text |Cite
|
Sign up to set email alerts
|

Limit cycles, noise, and chaos in hearing

Abstract: Based on insight obtained from a newly developed cochlea model, we argue that noise-driven limit cycles are the basic ingredient in the mammalian cochlea hearing process. For insect audition, we provide evidence in favor of the persistence of this principle. We emphasize the role of bifurcations for the emergence of broad-range sound perception, both in the frequency and amplitude domain, and indicate that this crucially depends on the correct coupling between limit cycles. We review the limit-cycle coupling u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Occasionally, mosquito antennae undergo spontaneous self-oscillations (6) that, in phase space, trace out an ellipse and are therefore quasisinusoidal (Fig. 3); this is in contrast to the limit cycles of, say, Drosophila, whose antennal limit cycle is of a relaxation type (20). Systems with limit cycles that are quasisinusoidal are practically equivalent to linear oscillators with weak nonlinear perturbations, and as such, the mosquito antennal auditory system can be considered to be weakly nonlinear (12).…”
mentioning
confidence: 99%
“…Occasionally, mosquito antennae undergo spontaneous self-oscillations (6) that, in phase space, trace out an ellipse and are therefore quasisinusoidal (Fig. 3); this is in contrast to the limit cycles of, say, Drosophila, whose antennal limit cycle is of a relaxation type (20). Systems with limit cycles that are quasisinusoidal are practically equivalent to linear oscillators with weak nonlinear perturbations, and as such, the mosquito antennal auditory system can be considered to be weakly nonlinear (12).…”
mentioning
confidence: 99%
“…37,38 Chaos may also be responsible for the anti-reliability of neurons. 22,39 However, in the present work, we have demonstrated that chaos is beneficial to sensory detection by hair cells. The dynamic state of a chaotic system depends sensitively on its initial conditions, and hence a small perturbation can result in a drastic change in the subsequent dynamics.…”
Section: Discussionmentioning
confidence: 45%
“…For example, a chaotic heartbeat is an indicator of cardiac fibrillation 39,40 . Chaos may also be responsible for the anti-reliability of neurons 24,41 . However, in the present work, we have demonstrated that chaos is beneficial to sensory detection by hair cells.…”
Section: Discussionmentioning
confidence: 99%
“…Physiological evidence exists for this active audition due to Hopf bifurcations for a range of animals and insect auditory systems [8][9][10][11]. Models have also been proposed which make use of coupling between limit cycles, which result from Hopf bifurcations, to produce significant amplification in insect hearing [12,13].…”
mentioning
confidence: 99%